MENINGKATKAN PRESTASI BELAJAR MATEMATIKA TENTANG PECAHAN SEDERHANA DAN PENGGUNAANNYA DALAM PEMECAHAN MASALAH MELALUI PENGGUNAAN MEDIA MANIPULATIF - Parti Parti (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2016)
The purpose of this study was to determine the increase of mathematics achievement of simple fractions and it’s use in solving problem through manipulation media. This study used classroom action research that consisted of several cycles with each cycle there are planning, action, observation, and reflection. The subjects were the third graders of The State Elementary School of Doyomulyo, Kembangbahu District, Lamongan in the academic year of 2015/2016, which has 21 students. The result showed that the use of manipulative media objects can improve the quality of teacher’s learning and improve the students’ learning completeness of third graders of The State Elementary School of Doyomulyo, Kembangbahu District, Lamongan. The number of students who complete the first cycle was 13 students to 18 students in the second cycle. The learning Mastery increased from 66.66% in the first cycle to 88.88% in the second cycle.